Museums and Photography: Displaying Death - Stylianou-Lambert, Theopisti (My University, 2017)
Museums and Photography adopts a strong theoretical approach in an in-depth investigation of the distinct approaches that different museums employ in displaying photographs of death, considering a broad range of anthropology, history, art, ethnographic, and science collections. These often interrelated approaches include: evidencing the past, death as spectacle, restoring anonymity and instigating empathy, and museums as agents of change. As well as offering fresh insights into the varied museum strategies implemented for the photographic display of death, the editors also critically engage with recent debates concerning the changing role of museums and museums' responsibility in handling an immensely controversial photographic genre
Keywords: museums; photography; death